1984
DOI: 10.1021/jm00374a011
|View full text |Cite
|
Sign up to set email alerts
|

cis-1,3,4,6,7,11b-Hexahydro-2-methyl-7-phenyl-2H-pyrazino[2,1-a]isoquinoline: a new atypical antidepressant

Abstract: Molecular modelling studies suggested the synthesis of cis-1,3,4,6,7, 11b-hexahydro-2-methyl-7-phenyl-2H-pyrazino[2,1-a]isoquinoline (7a) as a rigid analogue of the atypical antidepressant mianserin. Acylation of 2,2-diphenylethylamine with chloroacetyl chloride gives the chloroacetamide (2). Cyclization of 2 with P2O5 in xylene provides 1-(chloromethyl)-3,4-dihydro-4-phenylisoquinoline (3). Amination of 3, followed by reduction, gives the isomeric (aminomethyl)tetrahydroisoquinolines (4a and 5). Treatment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Based on the pharmacophoric model deduced, two novel structures with the predicted activity were prepared. Griffith et al (82) developed a novel atypical antidepressant based on a three-dimensional model of classical tricyclic antidepressants and mianserin. Martin & Kim (83) described the application of molecular modeling and QSAR reasoning that aided the development of a new class of diuretics (84).…”
Section: Receptor Site By Deductionmentioning
confidence: 99%
“…Based on the pharmacophoric model deduced, two novel structures with the predicted activity were prepared. Griffith et al (82) developed a novel atypical antidepressant based on a three-dimensional model of classical tricyclic antidepressants and mianserin. Martin & Kim (83) described the application of molecular modeling and QSAR reasoning that aided the development of a new class of diuretics (84).…”
Section: Receptor Site By Deductionmentioning
confidence: 99%
“…However, it should be noted that the antidepressant properties of 93 do not appear to be similar to those found for our series, in that 93 does not inhibit DA or NE uptake and binds to the muscarinic cholinergic receptor. 35 The pyrroloisoquinolines and the 4-phenyltetrahydroisoquinolines also bear a structural likeness to l-amino-3-phenylindan (e.g., 90)29 and l-amino-4-phenyltetralin (e.g., 91)28 antidepressants, a comparison that has been effectively discussed by Bogeso et al 29a Suffice it to say that compounds with both the cis and trans relative stereochemistry in these latter series show some antidepressant-like character, although there are some differences in selectivity for neurotransmitter uptake sites. Nevertheless, for biological activity the absolute stereochemistry at the center linked to the appended aryl group is invariably S (i.e., 4S or 3S, respectively).…”
Section: ! X =mentioning
confidence: 99%
“…Shekhter and colleagues in 1985 studied the reaction of 1-(aminomethyl)-1,2,3,4tetrahydroisoquinoline with diethyl fumarate, and found that cyclization proceeded through a Michael addition/amidation sequence, giving rise to two different pyrazino[2,1a]isoquinoline regioisomers in a 3:2 ratio. 18 Griffith et al (1984), starting from 2,2-diphenylethylamine, developed a short diastereoselective route (based on a Bischler-Napieralski reaction as the key step) to access various 2-alkyl-7-arylpyrazino[2,1-a]isoquinolines, which could also be obtained in enantiopure form after resolution. The authors evaluated the new compounds as atypical antidepressants by means of in vitro and in vivo studies, and found that their activity was comparable with those of well-established bioactive molecules such as imipramine and mianserin.…”
Section: Scheme 2 Synthesis Of Racemic Praziquantel Developed By E Mmentioning
confidence: 99%
“…The authors evaluated the new compounds as atypical antidepressants by means of in vitro and in vivo studies, and found that their activity was comparable with those of well-established bioactive molecules such as imipramine and mianserin. 19 Finally, two recent syntheses of praziquantel deserve a special mention, since they described two original methods to access the intermediate 1-(aminomethyl)tetrahydroisoquinoline. Starting from 2-PMP-tetrahydroisoquinoline 8, in 2013 Todd and co-workers applied a DDQ-mediated cross-dehydrogenative coupling with nitroalkanes to obtain compounds 9a,b, followed by reduction of the nitro group with Raney nickel and N-acylation to obtain intermediates 10a,b.…”
Section: Scheme 2 Synthesis Of Racemic Praziquantel Developed By E Mmentioning
confidence: 99%